Taller de aerografía implementando un estilo moderno e innovador, para la nueva comunidad artística popular guayaquileña - Alvear Lozano, Henry Miguel (2022)
Airbrushing has taken a leading role as an artistic trend, in the city of Guayaquil, however, its development is slowed by a wrong image product of constant confusion with the graffiti themselves that were coined by gang members, who are arranged as obscene graphics and phrases on public and private property. Based on this situation, these arts have been displaced, without taking into account the potential they have in their finishes and styles, which would generate a positive impact on the comfort of society, if they were adapted to interior design, which, Currently it is not possible because there are no properly adapted workshops to develop or perfect these skills, which is why it is established that the general objective of the research is "Designing an Airbrushing Workshop within the reach of the popular classes, with a modern style to through innovative materials, for a suitable environment for the adaptation of Aerographic Arts to the area of interior design…….